Profil of Sumedang Sport Climbing Athlete - A. R. Feliansyah Wiguna; Indra Safari; Rizal Ahmad Fauzi (Universitas Negeri Semarang, 2024)
There are many sport climbing athletes in Sumedang. However, the level of motivation to achieve is still low, as seen from the achievements and intensity of the training they do. So there is a need for a figure to serve as a reference in order to increase motivation to excel as athletes. This research aims to determine the profile of sport climbing athletes from Sumedang who have reached international levels. Using a descriptive approach with qualitative methods, research was conducted on sport climbing athletes from Sumedang, selected based on international-level achievements using purposeful sampling. The instruments used to collect information regarding athlete profiles include observation, interviews, and documentation stages. The procedure begins with the stage of direct observation of athletes during training, followed by interviews with athletes and carrying out documentation. The data was analyzed using the Miles and Huberman research design. These findings show several factors that support athletes' achievements. Motivational factors have the most influence on achieving achievement. The novelty of this research lies in the title and subject studied. Overall, the findings of this research contribute to motivation so that the achievements of Sumedang sport climbing athletes increase to reach international levels.